Calagem e adubação potássica para o capim-tifton 85 - Coutinho, Edson Luiz Mendes [UNESP]; Franco, Henrique Coutinho Junqueira; Orioli Júnior, Valdeci; Pasquetto, João Vitor Gomes [UNESP]; Pereira, Leonardo Salvador [UNESP] (My University, 2014)
Despite the high nutritional requirements of Tifton 85 grass, often the importance of liming and potassium fertilization for this forage has been neglected. In order to evaluate the effects of such practices on shoots dry matter and tillering of this forage, was carried out an experiment in green-house conditions, by two cuts, using samples of an Oxisol medium texture and a sandy soil. Efforts were also made to determine parameters to support recommendations for liming and potassium fertilization. Was adopted the completely randomized design with four replications in a factorial scheme 4x4x2, with four K rates (0, 60, 120 and 180 mg kg-1K), four pH values (original, 4.9, 5.9 and 6.4) and two soils. Potassium fertilization and liming promoted a significant increase in shoot dry matter and tillering in Tifton 85 grass, in both soils and cuts. The highest yields of shoot dry matter were associated with a base saturation of 56% and pH 5.2. The critical levels of K in soil and plant were 1.7 mmol dm-3and 14.0 g kg-1, respectively.
Liming and potassium fertilization for tifton 85 grass
Keywords: Base saturation; Critical level; Cynodon; pH; Potassium